Recreation potential assessment at large spatial scales: A method based in the ecosystem services approach and landscape metrics - Weyland, Federico (2014)
Ecosystem services (ES) is a useful framework for land-use decision making oriented to, ensure human well-being. Outdoor recreation potential, as a cultural ecosystem service, pose, particular challenges to its evaluation and mapping: it depends to a greater extent that other ES on, stakeholderś perception and values, it has lower generalization capacity, the delimitation of, provisioning areas is not straightforward and it should be evaluated at different spatial scales. In this, study, we propose a conceptual framework and method that is intended to cope with these challenges. Our method is based on landscape metrics measured at coarse scale, and campsite density as an, indicator of ecosystem service supply and benefit capture. We applied this method to a case study in, Argentina. We estimated outdoor recreation potential level using a quantile multiple regression, analysis of the 0.9 quantile of campsite density with nine landscape metrics determinants of ecosystem, service supply. We also explored two determinants of benefit capture with a linear stepwise regression, analysis of differences between the predicted recreation potential and actual use. We stratified the, analysis by ecoregion to distinguish the different weight of determinants of ecosystem service supply, and benefit capture. The examined landscape determinants showed differences in their explicative capacity of outdoor, recreation potential across ecoregions, showing that their generalization capacity is limited. For, example, and contrary to our expectations, crop area did not have a negative effect for any of the 15, analyzed ecoregions. In fact, significant correlations are positive for three cases. Forest cover, on the, other hand, had a positive effect only in the Pampas ecoregion, originally dominated by grasslands and, where current forests consist in plantations of exotic trees. Results also showed that, in general, unrealized benefit increases with road and population density. Our method makes a contribution to the study of recreation potential under the framework of ES by, taking into account important aspects that are sometimes overlooked. It considers the differences with, other ecosystem services in terms of the underlying processes that control ecosystem service supply, and benefit capture and it can be applied at a very wide spatial extent, at which approaches with other, methods that are more information demanding is difficult. Yet complementary methods at more, detailed spatial scales would provide additional information for a comprehensive estimation of, outdoor recreation potential.